Karakteristik dalam Komunikasi Politik Mengemas Pesan Politik - Winda Kustiawan; Ahmad Fauzi; Daffaul Haqqi; M. Saripuddin; Ridho Khairul Imam; Rani Puspita (Universitas Muhammadiyah Enrekang, 2022)
Communication can be easily defined either as a process by which a communicator sends a message to a host with or without information leading to a special event. In terms of politics, political communication can be a very valuable thing because it provides and receiving messages. This paper contains about Communication In Packaging Political Massages which include mass channels, interpersonal channels and organizational channels. As for the research method in the form of a qualitative approach using a descriptive method. With keyword Characteristics, Communication, Politics.